Monitoring of SARS-CoV 2 on primary production and manually processed foods in Northern Italy. (20th October 2021) - Bertasi, B; Galuppini, E; Tilola, M; Mangeri, L; Meletti, F; Righi, F; Scarazzato, A; Pavoni, E; Losio, MN
Abstract: Background: SARS CoV2 pandemic has generated interest in research of virus spread sources, apart from human contagion. In particular different studies are performed to understand surfaces involvement; during the epidemic event, different types of studies on surfaces have been performed. However, there is little information regarding the presence of the virus in food; wastewater contamination and poor hygiene practices could be the sources of viral contamination in handled food products. The aim of this work was to analyze different types of food for Sars CoV 2 presence. Methods: 390 samples of molluscs, 353 vegetables, 10 meat, 72 water, 169 berries, 16 seafood products and ready-to-eat dishes were analysed (2020-2021). Samples were selected from those provided for routine analysis during the pandemic period. The preparation was done based on ISO 15216-2 indications, followed by extraction with Nuclisense®Minimag® system; real-time PCR was applied to detect the Sars CoV2 virus Open Reading Frame 1ab, with two different master mixes. Results: All samples tested were negative for ORF1ab detection. Many hypothesis can be made about negative Results: it could be possible that contamination levels in water, or on surfaces in contact with food, are too low to generate a detection signal; again, handling practices may be sufficient to avoid the transmission of the virus to food. Otherwise, the selected genetic target and the Real-time PCR performed, could have been not so efficient in detecting virus as expected. Conclusions: In this preliminary work, food does not seem to be a substrate for Sars CoV2 contamination; other food categories or transformation/production processes could be investigated to confirm the obtained results. Also, different targets and amplification systems would have to be evaluated to verify the rule of foodstuffs as Sars CoV2 vehicles. Key messages: Primary production and manual processed food don't seem to be at risk for SARS CoV2 contamination. Food has not been identified as a source of Sars CoV2 spreading.